A Kind of Compact Quantum Semigroups - Maysam Maysami Sadr (International Journal of Mathematics and Mathematical Sciences)
We show that the quantum family of all maps from a finite space to a finite-dimensional compact quantum semigroup has a canonical quantum semigroup structure.